2022
DOI: 10.1021/acsami.2c04378
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Integrated Bionic Oxygenated Scaffold for Bone Regeneration

Abstract: The repair of large bone defects remains a challenging problem in bone tissue engineering. Ischemia and hypoxia in the bone defect area make it difficult for seed cells to survive and differentiate, which fail to perform effective tissue regeneration. Current oxygen-producing materials frequently encounter problems such as a rapid degradation rate, insufficient mechanical properties, difficult molding, and cumbersome fabrication. Here, a novel three-dimensional (3D) printed integrated bionic oxygenated scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Compared to non-oxygenated scaffolds, the oxygenated scaffolds exhibit favourable mechanical properties, promote MSC survival in hypoxic conditions, and enhance MSC proliferation and osteogenic differentiation, resulting in enhanced bone regeneration at 4 and 12 weeks after implantation in a rabbit cranial defect. 231…”
Section: Biomaterials For Msc Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-oxygenated scaffolds, the oxygenated scaffolds exhibit favourable mechanical properties, promote MSC survival in hypoxic conditions, and enhance MSC proliferation and osteogenic differentiation, resulting in enhanced bone regeneration at 4 and 12 weeks after implantation in a rabbit cranial defect. 231…”
Section: Biomaterials For Msc Transplantationmentioning
confidence: 99%
“…Compared to nonoxygenated scaffolds, the oxygenated scaffolds exhibit favourable mechanical properties, promote MSC survival in hypoxic conditions, and enhance MSC proliferation and osteogenic differentiation, resulting in enhanced bone regeneration at 4 and 12 weeks after implantation in a rabbit cranial defect. 231 A major therapeutic mechanism of MSCs is their secretion of extracellular vesicles (EV), which carry a range of intercellular signalling factors. Scaffolds can be designed to not only improve cell retention and survival, but also promote EV secretion.…”
Section: Implantable Msc-laden Biomaterialsmentioning
confidence: 99%
“…Another study demonstrated that nHA/chitosan composite microspheres added to chitosan membranes can significantly enhance the mechanical strength of materials with strong spatial maintenance ability and bionic function, and effectively promote the recovery of bone defects [64]. Recently, a bionic oxygenated scaffold was fabricated using gelatin-CaO 2 microspheres, polycaprolactone, and nHA, which could release oxygen continuously for more than 2 weeks, thus improving the survival, growth and osteogenic differentiation of MSCs under hypoxic conditions [65]. Moreover, gelatin/CaO 2 microspheres acted as a pressure dispersion conductor within the scaffold, approaching the compressive strength of the natural bone cortex at week 12.…”
Section: Biomimetic Construction Of the In Vivo Microenvironmentmentioning
confidence: 99%
“…30,31 The NFs structure has been widely studied in the field of catalysis and chemistry; 10 however, it is less reported in regard to biomedical applications. Most highlighted is the bioactive capacity of the NFs, with the constituents of calcium, phosphate and gelatin, which resemble components of bone tissue and might be "bionic" 32 for the bone remodeling procedure. Interestingly, this flower-like structure could release bioactive ions including Ca 2+ and PO 4 3− for the joint bone remodeling process.…”
mentioning
confidence: 99%
“…Flower-like structures are defined as hierarchical morphologies, with high specific surface area, porous structure, and capacity of substance adsorption and capture. , The NFs structure has been widely studied in the field of catalysis and chemistry; however, it is less reported in regard to biomedical applications. Most highlighted is the bioactive capacity of the NFs, with the constituents of calcium, phosphate and gelatin, which resemble components of bone tissue and might be “bionic” for the bone remodeling procedure. Interestingly, this flower-like structure could release bioactive ions including Ca 2+ and PO 4 3– for the joint bone remodeling process. , The Ca 2+ released from flower also could create the in situ biomineralization layer, thus providing an “osteogenic microenvironment” for the BMSCs’ osteogenic induction .…”
mentioning
confidence: 99%